Point‐of‐Care Ultrasound for Hospitalists: A Position Statement of the Society of Hospital Medicine. Issue 1 (2nd January 2019) - Soni, Nilam J.; Schnobrich, Daniel; Mathews, Benji K.; Tierney, David M.; Jensen, Trevor P.; Dancel, Ria; Cho, Joel; Dversdal, Renee K.; Mints, Gregory; Bhagra, Anjali; Reierson, Kreegan; Kurian, Linda M.; et al.
Abstract : Many hospitalists incorporate point‐of‐care ultrasound (POCUS) into their daily practice to answer specific diagnostic questions or to guide performance of invasive bedside procedures. However, standards for hospitalists in POCUS training and assessment are not yet established. Most internal medicine residency training programs, the major pipeline for incoming hospitalists, have only recently begun to incorporate POCUS in their curricula. The purpose of this document is to inform a broad audience on what POCUS is and how hospitalists are using it. This document is intended to provide guidance for the hospitalists who use POCUS and administrators who oversee its use. We discuss POCUS 1) applications, 2) training, 3) assessments, and 4) program management. Practicing hospitalists must continue to collaborate with their local credentialing bodies to outline requirements for POCUS use. Hospitalists should be integrally involved in decision‐making processes surrounding POCUS program management.